Status and Determinants of Women’s Participation in Household Decision Making in Ethiopia - Melkamu; Addis (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2021)
Women's participation in household decision making has a pivotal role to the development of coun- tries. At a national level, studying the status of women's participation in household decision mak- ing and its determinants is necessary to devise policies and take immediate measures to empow- er women. Therefore, this study was aimed at assessing the status and determinants of women's participation in household decision making in Ethiopia. A cross-sectional study based on data from the 2016 Ethiopian Demographic and Health Survey (EDHS) program was employed. The sample was limited on married women (N=3676) and analyzed through binary logistic regression. The finding revealed that the majority (63.87%) of women were found relatively in a good position of participation in household decision making. Education and employment were positively associated with their participation. Women who never fear their husbands (AOR=1.391;95%CI=1.196,1.618) and women who did not refuse sexual intercourse (AOR=1.384;95%CI=1.192,1.606) were more likely participate in household decision making. There were variations of women's participa- tion in household decision making as to religious affiliation and geographical location. In conclu- sion, the status of women's participation in household decision making in Ethiopia is relatively good albeit taking some proper interventions are still necessary to address the existing gaps.